Al-Qaeda grows in Africa : new union with Al Shabaab - Rohan Gunaratna (2012)
Al Shabaab presents a growing threat to Somalia. After it formalised its association with al-Qaeda, the momentum of attacks, especially suicide attacks, increased. By making inroads to Africa, al Qaeda will exploit Al Shabaab’s long standing links with like-minded threat groups in a fragile continent.